An effect of arbuscular mycorrhiza on Phaseolus vulgaris L. and Zea mays L. root system morphology (Experimental biology, 2015)
Investigations of the mycorrhizal and nonmycorrhizal plants Phaseolus vulgaris L. and Zea mays L. showed that root systems of plants with mycorrhiza were developed more better than nonmycorrhizal ones.Received data show that arbusclular mycorrhiza raises the growth characteristics of host plant considerably increasing the number and the length of as main as additional roots. Owing to the increasing of the rootsystem capacity the volume of used soil is increased too. This increases the abundance of nutritive material available to host plant. Hence, the persistence of plants and its resistance to difficult environments.
Keywords: arbuscular mycorrhiza; root system morphology; Phaseolus vulgaris L.; Zea mays L.; primary root system; adventitious root system; host plant; Glomus genus